Functional distribution and wage inequality in recent Kaleckian growth models - Eckhard Hein; Franz Prante (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2018)
This contribution provides a review of recent considerations of wage inequality in Kaleckian models of distribution and growth. On the one hand, we address modelling approaches in which a distinction is made between managers and workers, where the salaries of the former are treated as overhead costs in a target-return pricing framework. Distribution between profits and wages, and between managers and direct labour, will thus depend on the level of economic activity, in particular in a short-run cyclical perspective. On the other hand, we review more recent Kaleckian models, which explicitly introduce wage inequality, but maintain the simple mark-up pricing approach, thus abstracting from explicit consideration of overhead costs. Explicitly or implicitly, these models rather adhere to a medium-run perspective. Finally, we provide a simple neo-Kaleckian distribution and growth model with wage inequality, which allows for different medium-run demand regimes in a stylized way.
Keywords: E12; E25; D31; 330; functional income distribution; wage inequality; distribution; growth; Kaleckian models